2001
DOI: 10.4315/0362-028x-64.11.1744
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Immunomagnetic Separation and Polymerase Chain Reaction for the Simultaneous Detection of Listeria monocytogenes and Salmonella spp. in Food Samples

Abstract: A method that combined the immunomagnetic separation (IMS) technique and the multiplex polymerase chain reaction (PCR) method (i.e., the IMS-mPCR method) was developed for simultaneous detection of Listreria monocytogenes and Salmonella spp. in food samples. When only the multiplex PCR method was used, it was found that if cell numbers of each of the two target organisms (L. monocytogenes and Salmonella spp.) were above the detection limit, but differed by more than 2 logs-e.g., n x 10(7) to n x 10(4) or n x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 30 publications
1
35
0
1
Order By: Relevance
“…Immunomagnetic separation (IMS) has been previously applied to isolation of microorganisms (Grant et al, 1998;Hsih and Tsen, 2001;Pinto and Tantillo, 2002). Madonna et al (2001) also reported isolation of Salmonella choleraesuis from a variety of matrices including river water, urine and chicken blood.…”
Section: Immunomagnetic Separationmentioning
confidence: 97%
“…Immunomagnetic separation (IMS) has been previously applied to isolation of microorganisms (Grant et al, 1998;Hsih and Tsen, 2001;Pinto and Tantillo, 2002). Madonna et al (2001) also reported isolation of Salmonella choleraesuis from a variety of matrices including river water, urine and chicken blood.…”
Section: Immunomagnetic Separationmentioning
confidence: 97%
“…Magnetic separation (MS) has become a routine method in food and veterinary microbiology laboratories and is commonly used in combination with culture or molecular methods for the detection and isolation of pathogenic bacteria such as Listeria monocytogenes (13,31), Salmonella spp. (22,25), and Escherichia coli O157:H7 in both the food (15) and veterinary (20) clinical sample testing context.…”
mentioning
confidence: 99%
“…The results described here indicate that the MAAB not only has similar or better detection limits than other sensors, but also requires only 15 min for analysis of prepared samples. Sample processing is simple, requiring only homogenization of the foodstuff or excreta, followed by coarse filtration or centrifugation; this ease of sample preparation contrasts greatly with the large numbers of manipulations typically required for nucleic acid-based techniques (6,10,31), even with immunomagnetic separation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a pre-enrichment step is typically required to increase the number of viable cells while effectively diluting inhibitory substances present in the sample. A large number of papers describing PCR-based detection of Salmonella from spiked or naturally contaminated foods have claimed LODs ranging from 0.1 to 100 CFU/g (6,10,31,37,40). However, many of these LODs represent the concentrations of inoculum used rather than actual bacterial counts after enrichment; postenrichment concentrations can reach 10 6 to 10 9 CFU/ml (6,7,17,23).…”
Section: Discussionmentioning
confidence: 99%